SPORT AND LAW - Afrim Berisha; Mexhid Krasniqi; Blerim Sylejmani; Lirjata Gjuraj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This work offers a review of law implementation in sport. It present a number of cases which should be dealt with regarding the established legal regulation for providing with law protection athletes, coaches, sports workers and sports clubs.